Complete embolization of jugular paragangliomas by direct puncture. Technical note. (4th May 2019) - Rustemi, Oriela; Raneri, Fabio; Volpin, Lorenzo; Iannucci, Giuseppe
Abstract: Objective: Intra-arterial embolization of jugular paragangliomas is an established endovascular technique. Intratumoral embolization by direct puncture has been proposed, prior to surgical treatment or radiosurgery to reduce the risk of cranial nerve deficits. Methods: We examined the technical aspects of two patients with jugular paragangliomas embolized with liquid embolic agent by direct puncture of the lesion, as sole treatment. Results: Two patients with jugular paragangliomas presented with lower cranial nerve deficits. The first patient showed an extended lesion (55-mm) and was treated with partial intra-arterial embolization plus direct puncture and injection of Squid 18 and a second staged embolization by direct puncture and filling of the remainder of the lesion. The second patient with a smaller jugular paraganglioma (33-mm) was treated by single embolization by direct puncture of the tumor and injection of Squid 12 and Squid 18 obtaining complete filling of the lesion. No procedural complications were observed. Both patients showed no residual and initial improvement of the neurological deficits. Conclusion: The intratumoral embolization by direct puncture of jugular paragangliomas, under accurate radiological control is a safe procedure, and complete exclusion of the lesion can be obtained in selected cases. A staged particle embolization of the lesion by direct puncture can be proposed for large lesions. Only further studies with larger series and long-term follow-up will be able to define, if this strategy can be curative avoiding additional surgical or radio-surgical treatment.